Pengaruh Penambahan Konsentrasi Minyak Atsiri Nilam (Pogostemon cablin B.) Pada Formulasi Pembuatan Sampo Cair - Widyasanti, Asri; Hafyyan, Muhammad; Rosalinda, S (Universitas Trunojoyo Madura, 2025)
Shampoo is a personal care product formulated to cleanse and maintain the health of hair and scalp by removing impurities. Indonesia has significant potential to capture a share of the global shampoo market by leveraging its natural resources and traditional herbal ingredients. Patchouli essential oil, a notable ingredient in Indonesian products, contains patchouli alcohol, which serves as an effective antibacterial agent. This study aimed to examine the impact of incorporating light fraction patchouli oil into a liquid shampoo formulation and to evaluate the quality of the patchouli oil shampoo in accordance with the Indonesian National Standard (SNI) Shampoo 06-2692-1992. The research employed a laboratory-based experimental approach using a Completely Randomized Design (CRD). Treatments involved varying concentrations of patchouli oil added to the shampoo formulation: Z (0%), A (1.0%) (w/w), B (1.25%) (w/w), C (1.5%) (w/w), D (1.75%) (w/w), and E (2.0%) (w/w). The evaluation parameters included yield, moisture content, pH level, organoleptic properties, and antibacterial activity. Among the formulations, the shampoo with a 1.0% (w/w) concentration of patchouli oil (Treatment A) was identified as the optimal formula, with a yield of 87.122%, moisture content of 63.59%, pH of 6.74, and the highest bacterial inhibition zone at 16.75 mm. Results indicated that increasing the concentration of patchouli oil resulted in higher moisture content and pH levels, while yield and antibacterial activity decreased. All treatments met the standards set by SNI Shampoo 06-2692-1992, demonstrating that the addition of light fraction patchouli oil is effective and beneficial as a functional component in shampoo production.